International R&D spillovers and productivity growth in the Asean countries - NurNaddia Nordin; Normaz Wana Ismail; NurHaiza Nordin (2016)
The aim of this study is to examine the role of international R&D spillovers for the ASEAN countries. The dynamic ordinary least square panel estimator (DOLS) is employed using data from 1996 to 2012. The important conclusions that can be drawn from the reported results are import is the main channel for international R&D spillovers in ASEAN countries. Therefore, policymakers and governments should play an important role in promoting trade activity and other policies that related with trade especially import activities as both are expected to boost host country productivity.